2019
DOI: 10.1021/acs.cgd.9b01067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functionalized Multiwalled CNTs on the Selective Formation of Calcium Oxalate Crystals by Electrocrystallization

Abstract: The electrocrystallization (EC) of calcium oxalate (CaOx) crystals in the presence of multiwalled carbon nanotubes (MWCNTs) functionalized with itaconic acid (IA) and the monoester derivatives monomethylitaconate or mono-octadecylitaconate, which were used as new IA-ester templates supported on indium tin oxide glass substrate as working electrode, was performed by applying a 9 mA current at 37 and 60 °C for 5 min. Under the above EC reaction conditions, a broad variety of CaOx morphologies and crystal forms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The COD form is often present in the urine of healthy subjects while COM calculi are more prevalent in the urine of recurrent stone formers compared with urine from healthy subjects [14,15]. Thus, recent reports focused on how natural and synthetic additives, for example, amino acids [16][17][18][19], polymers [20,21], lipids [22], proteins [23,24], peptides [25,26], metal ions [27][28][29], and carboxylic acids [30,31], affect the formation of the different forms of CaOx and how they can be leveraged to prevent or treat kidney stones. Various additives show specific binding with different surfaces of the CaOx crystals and can inhibit their growth via various mechanisms [32].…”
Section: Introductionmentioning
confidence: 99%
“…The COD form is often present in the urine of healthy subjects while COM calculi are more prevalent in the urine of recurrent stone formers compared with urine from healthy subjects [14,15]. Thus, recent reports focused on how natural and synthetic additives, for example, amino acids [16][17][18][19], polymers [20,21], lipids [22], proteins [23,24], peptides [25,26], metal ions [27][28][29], and carboxylic acids [30,31], affect the formation of the different forms of CaOx and how they can be leveraged to prevent or treat kidney stones. Various additives show specific binding with different surfaces of the CaOx crystals and can inhibit their growth via various mechanisms [32].…”
Section: Introductionmentioning
confidence: 99%
“…Crystal growth modifiers are small amounts of additives that can be used to either promote or inhibit crystallization/transformation processes. Several types of additives, such as amino acids [21][22][23][24][25][26][27][28], proteins [29,30], carboxylic acids [31][32][33] and polymers [34][35][36] have been shown to affect CaOx crystallization. In addition, studies have shown that peptides containing aspartic acidglutamic acid, glutamic acid-glutamic acid, alanine-aspartic acid amino acids have a profound effect on the CaOx crystals and could promote the formation of COD and COT crystals and stabilize these metastable phases over very long periods of time [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%